Analisis Tingkat Kepuasan Kemitraan Peternak Plasma Terhadap Pelayanan PT. Great Giant Livestock (GGL) - Elisa Mirayana; Supriyadi Supriyadi; Ainul Mardliyah (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2020)
This study aims to analyze the satisfaction of plasma farmers with PT GGL services in the village of Astomulyo, Punggur District, Central Lampung Regency. The research method used is descriptive analysis method, plasma farmers satisfaction analysis using the Customer Satisfaction Index (CSI) Analysis. The research location is in Astomulyo village, Punggur Subdistrict, Central Lampung. When the study was conducted in October-November 2019. Determination of the sample using a survey method in which a sample of 50 people. The results of the study concluded that the level of satisfaction of plasma farmers with PT GGL services in Astomulyo Village, Punggur District, Central Lampung Regency was very satisfied.